Seed Germination and Seed Bank Dynamics of Eruca sativa (Brassicaceae): A Weed on the Northeastern Edge of Tibetan Plateau - Jia, Cun-Zhi; Wang, Jing-Jing; Chen, Da-Li; Hu, Xiao-Wen (Frontiers in Plant Science, 2022)
As a versatile cruciferous species, Eruca sativa is widely cultivated, but in some areas, it has become an invasive weed. There are few studies on its seed dormancy and soil seed bank. This research examined seed dormancy, germination, and dynamics of the soil seed bank of E. sativa, with a view to provide support for its prevention and control. We tested the effects of temperature, light, storage, water, and salinity stress on seed germination and burial depth on seedling emergence of E. sativa. Dynamics of the soil seed bank were determined with a 24 month in situ seed-burial study. Seeds of E. sativa can germinate in a temperature range of 5–35°C; moreover, they exhibited non-deep physiological dormancy (NDPD) at maturity, which can be broken by dry storage or exposure to low temperature in winter. Germination of E. sativa seeds was sensitive to water and salinity stress, and most seeds did not germinate at -0.3 MPa. When buried in soil in the field, seeds exhibited an annual dormancy/non-dormancy cycle and formed at least a short-term persistent soil seed bank. Seeds buried deeper than 5 cm can hardly emerge. Seeds of E. sativa have a wide germination temperature range and exhibited dormancy cycling, which promotes the formation of a persistent soil seed bank and enables it to better adapt to the harsh low-temperature climate of the Qinghai-Tibet Plateau. No-tillage would be a good management strategy for this species.